Implementasi Kebijakan Global Governance Pasca Pandemi Covid-19 dalam Pemulihan Ekonomi di Indonesia - Dhea Novita Putri; Ranti Astari Rahayu; Fauzan H; M. Biaggi; Noer Apptika Fujilestari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The research carried out aims to understand the implementation of Indonesia's Global Governance Policy after the pandemic based on Global Governance. After the Covid-19 pandemic, Indonesia faces a big challenge in the context of global governance. The policies taken aim to restore the economy, improve public health, and strengthen international cooperation. Data is collected through library surveys without the need for field surveys, but with data from books and periodical publications. Based on research findings, the analysis explores the steps taken by the Indonesian government, including the implementation of national economic recovery programs, capacity building of the health system, and participation in global initiatives. The results of the analysis show that although there is progress, challenges in coordination and resources still exist, which affect the imlementation of the policy. Sustainable efforts and international cooperation are the key to overcoming the long-term impact of the pandemic.